Introduction : novel insights into TB research and drug discovery - Grüber, Gerhard (2020)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), kills more people than any other bacterium. TB control is threatened by the continued spread of drug resistance; multi-drug and extensively drug resistant Mtb require longer, more costly, treatment with multiple drugs causing worse side effects and have a lower likelihood of treatment success. The urgent need for better treatment options for drug resistant Mtb has led the World Health Organization to prioritize development of not only new individual antitubercular agents, but also new drug regimens. This introductory chapter of the special issue Novel insights into TB research and drug discovery within Progress in Biophysics and Molecular Biology, gives a short overview about the general problems of TB and the treatment of this disease today, and introduces the review topics within this issue.